Clinical practice guidelines for the care of girls and women with Turner syndrome: proceedings from the 2016 Cincinnati International Turner Syndrome Meeting - Gravholt, Claus H; Andersen, Niels H; Conway, Gerard S; Dekkers, Olaf M; Geffner, Mitchell E; Klein, Karen O; Lin, Angela E; Mauras, Nelly; Quigley, Charmian A; Rubin, Karen; Sandberg, David E; Sas, Theo C J; et al. (European journal of endocrinology, 2017)
Turner syndrome affects 25-50 per 100,000 females and can involve multiple organs through all stages of life, necessitating multidisciplinary approach to care. Previous guidelines have highlighted this, but numerous important advances have been noted recently. These advances cover all specialty fields involved in the care of girls and women with TS. This paper is based on an international effort that started with exploratory meetings in 2014 in both Europe and the USA, and culminated with a Consensus Meeting held in Cincinnati, Ohio, USA in July 2016. Prior to this meeting, five groups each addressed important areas in TS care: 1) diagnostic and genetic issues, 2) growth and development during childhood and adolescence, 3) congenital and acquired cardiovascular disease, 4) transition and adult care, and 5) other comorbidities and neurocognitive issues. These groups produced proposals for the present guidelines. Additionally, four pertinent questions were submitted for formal GRADE (Grading of Recommendations, Assessment, Development and Evaluation) evaluation with a separate systematic review of the literature. These four questions related to the efficacy and most optimal treatment of short stature, infertility, hypertension, and hormonal replacement therapy. The guidelines project was initiated by the European Society for Endocrinology and the Pediatric Endocrine Society, in collaboration with The European Society for Pediatric Endocrinology, The Endocrine Society, European Society of Human Reproduction and Embryology, The American Heart Association, The Society for Endocrinology, and the European Society of Cardiology. The guideline has been formally endorsed by the European Society for Endocrinology, the Pediatric Endocrine Society, the European Society for Pediatric Endocrinology, the European Society of Human Reproduction and Embryology and the Endocrine Society. Advocacy groups appointed representatives who participated in pre-meeting discussions and in the consensus meeting.